2018
DOI: 10.1590/1678-4766e2018012
|View full text |Cite
|
Sign up to set email alerts
|

Pollination efficiency on Ipomoea bahiensis (Convolvulaceae): morphological and behavioural aspects of floral visitors

Abstract: Pollination depends on morphological and behavioural adjustments between visitors and plants. Some plant species as Ipomoea bahiensis (Convolvulaceae) provide nectar and pollen to visitors and occur in anthropic areas, therefore becoming an important source of resources for the maintenance of native pollinating insects. However, what is the efficiency of each floral visitor species for the pollination of this plant species? What morphological and behavioural characteristics determine the pollinators? In this r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 15 publications
(16 reference statements)
2
7
0
Order By: Relevance
“…When considering both foraging behavior and visitation rates, the likely pollinators of A. siamensis are stingless bees (Meliponini), blue-banded bees (Amegilla), and skipper butterflies (particularly U. folus). These results are consistent with previous research, as many species in the morning glory family are pollinated by bees and butterflies [12,13,17,30,[33][34][35][36][37][38][39][40][41][42][43]. Stingless bees are often abundant in tropical pollinator assemblages [44][45][46], including in Thailand [47][48][49], and many tropical species of morning glory are known to be pollinated by stingless bees, such as Ipomoea carica, I. grandifolia, and I. nil [36]; I. aquatica [43]; I. wolcottiana [12]; I. hieronymi [50]; Merremia aegyptia [33]; M. macrocalyx [20]; and M. dissecta var edentada [37].…”
Section: Pollinator Observationssupporting
confidence: 93%
See 1 more Smart Citation
“…When considering both foraging behavior and visitation rates, the likely pollinators of A. siamensis are stingless bees (Meliponini), blue-banded bees (Amegilla), and skipper butterflies (particularly U. folus). These results are consistent with previous research, as many species in the morning glory family are pollinated by bees and butterflies [12,13,17,30,[33][34][35][36][37][38][39][40][41][42][43]. Stingless bees are often abundant in tropical pollinator assemblages [44][45][46], including in Thailand [47][48][49], and many tropical species of morning glory are known to be pollinated by stingless bees, such as Ipomoea carica, I. grandifolia, and I. nil [36]; I. aquatica [43]; I. wolcottiana [12]; I. hieronymi [50]; Merremia aegyptia [33]; M. macrocalyx [20]; and M. dissecta var edentada [37].…”
Section: Pollinator Observationssupporting
confidence: 93%
“…Moreover, Kato et al [51] reported that, in Laos, Amegilla bees typically pollinate perennial, tubular flowers, which corresponds with the habit and morphology of our study species. Butterflies are also known to visit the flowers of Convolvulaceae species; however, they appear to be less important pollinators than bees due to their less reliable and infrequent visits [17,40,53]. Our results also indicate that skipper butterflies are less frequent visitors than bees, but they appear to be important pollinators in areas where bee visitation is low, as in the case we observed in the eastern population.…”
Section: Pollinator Observationssupporting
confidence: 53%
“…Given the positive correlation between body size and hair length, studies exploring the relationship between hairiness and pollination effectiveness should account for body size, which, along with flower‐handling behavior and visit duration, has also been shown to affect pollination effectiveness (Jauker et al, ; Kandori, ; Phillips et al, ; Willmer & Finlayson, ). Accordingly, in pollination studies, hairiness measures should target the body parts involved in pollen transfer, which depend on flower morphology, pollinator body size and intra‐floral foraging behavior (Araujo, Medina, & Gimenes, ; Beattie, Breedlove, & Ehrlich, ; Bosch, ; Solís‐Montero & Vallejo‐Marín, ).…”
Section: Discussionmentioning
confidence: 99%
“…Tubular flowers are generally expected to restrict entry into the floral tube to visitors of matching size. In the tubular flower of Ipomoea bahiensi s ( Convolvulaceae ), the close fit between the width of the floral tube and the length/width of the visitor is essential to ensure contact with reproductive structures and successful pollination (Araujo et al 2018). In Prunella vulgaris , while the pollinator enters its proboscis into the corolla tube for nectar collection, the dorsal surface of its head touches the anthers and stigma.…”
Section: Discussionmentioning
confidence: 99%